Empirical Regularities of Nigeria’s Foreign Private Portfolio Investment Return and Volatility - Ihejirika, Peters Omeni (Archives of Business Research, 2017)
ABSTRACT This paper examined the Empirical Regularities of Nigeria’s Foreign Private Portfolio Investment Return and Volatility. The study covered the periods between 1981 and 2014. An EGARCH model was specified. The analysis involves carrying out the tests for Financial Assets and Risk assumptions. The study revealed that Foreign Private Portfolio Investment Returns show Volatility clustering. Secondly, Foreign Private Portfolio Investment Return and Risk were found to have Thick tail. Variance Ratio Test [VRT] was used to test the weak form efficiency of the efficient market hypothesis and hence the non-predictability of financial markets. The Results showed that changes in one direction are more often followed by similar changes in either direction (volatility clustering). Given that Nigeria’s Foreign Private portfolio investment empirical imperatives is regular like that of the rest of the world, the paper thus recommends that investment decision models used by advanced analyst in developed countries can be applied to developing countries like Nigeria with little modification with respect to Foreign Private Portfolio Investment as their assets and risks display similar characteristics with assets and risks in developed countries.